Wear-resistant and corrosion-resistant composite TPE material for charging pile cable
By using crosslinked modified SEBS and wear-resistant and anti-aging fillers in charging pile cable materials, and introducing isocyanate-based crosslinked polymers, the problems of aging, corrosion and wear in outdoor use are solved, achieving higher weather resistance and service life.
Patent Information
- Application Number
- CN202510139728.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-04-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing charging pile cable materials are susceptible to ultraviolet radiation and mechanical stress during outdoor use, resulting in aging, corrosion and wear, reducing the material's weather resistance and service life.
The composite TPE material is adopted which is composed of 50 to 80 parts by weight of polypropylene, 30 to 40 parts by weight of crosslinked modified SEBS, 32 to 45 parts by weight of white oil, 10 to 25 parts by weight of ethylene-vinyl acetate copolymer, 3 to 12 parts by weight of wear-resistant and anti-aging filler, 2 to 5 parts by weight of antioxidant and 1 to 3 parts by weight of lubricant. The heat resistance and anti-aging corrosion performance of the material are improved by the introduction of isocyanate-based crosslinked polymer.
It significantly improves the mechanical strength, heat resistance and corrosion resistance of charging pile cable materials, extends the service life of the material, and improves its wear resistance in outdoor environments.
Smart Images

Figure BDA0005264428980000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and more specifically, to a wear-resistant and corrosion-resistant composite TPE material for charging pile cables. Background Art
[0002] SEBS triblock copolymer is a styrene-based thermoplastic elastomer. Compared with SBS, it is not easily oxidized and has excellent toughness, resilience and non-toxicity. Therefore, it has the potential for engineering applications in the field of wires and cables. However, SEBS is limited by its high price when used alone and its high processing viscosity, which makes it difficult to thermoform in traditional industries. It usually needs to be blended with other resins (such as polypropylene) or oil-filled during the processing process to prepare a composite TPE material, thereby improving its processing fluidity to meet industrial needs. Among them, although the blending of SEBS and polypropylene can obtain a composite TPE material with good mechanical properties, the introduction of polypropylene alone will reduce the elasticity of the composite TPE material. Therefore, in the prior art, oil filling processing is usually used to maintain the resilience of the composite TPE material. However, on the one hand, oil substances have high thermal conductivity, and the composite TPE material after oil filling is easier to transfer heat at high temperature, resulting in a faster rise in internal temperature, accelerating the aging and corrosion of the material, resulting in reduced heat stability and weather resistance and aging and corrosion resistance of the composite TPE material after oil filling. On the other hand, when oil substances are filled into the composite TPE material, the oil substances will preferentially dissolve in the soft segment of SEBS, causing the soft segment of SEBS to expand, destroying the original structural network of SEBS, reducing the crosslinking density of the entire material, and thus weakening the mechanical strength of the composite TPE material after oil filling. In order to improve the mechanical strength and heat stability of composite TPE materials, the main method at present is to fill inorganic fillers in composite TPE materials. However, the dispersibility and compatibility of inorganic fillers in composite TPE materials are poor, and they are easy to form agglomeration. Especially after oil filling, oil substances may further affect the dispersion of fillers and the fusion effect of fillers and composite TPE materials, and cannot effectively improve the mechanical properties and heat stability of composite TPE materials.
[0003] Charging piles are usually installed in outdoor environments, and charging pile cables are exposed to direct sunlight for a long time. Ultraviolet radiation will accelerate the aging process of charging pile cable materials, causing cracks and fading on the surface, affecting the anti-aging and corrosion performance of charging pile cable materials and reducing the service life of the materials. In addition, charging pile cables are often subjected to mechanical stress such as vehicle rolling and dragging. Charging pile cable materials have poor wear resistance, which can easily cause wear or scratches, shorten the service life of the cables, and increase the failure rate. Therefore, in order to meet the performance requirements of charging pile cables, it is of great significance to develop a composite TPE material with good mechanical strength, heat stability, anti-aging and corrosion performance, and wear resistance. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a wear-resistant and corrosion-resistant composite TPE material for charging pile cables.
[0005] A wear-resistant and corrosion-resistant composite TPE material for charging pile cables, the composite TPE material is composed of the following components:
[0006] 50-80 parts by weight of polypropylene, 30-40 parts by weight of crosslinked modified SEBS, 32-45 parts by weight of white oil, 10-25 parts by weight of ethylene-vinyl acetate copolymer, 3-12 parts by weight of wear-resistant and anti-aging filler, 2-5 parts by weight of antioxidant and 1-3 parts by weight of lubricant;
[0007] The raw materials of cross-linked modified SEBS include: hydroxylated modified SEBS solution, isocyanate-based cross-linked polymer and dibutyltin dilaurate, wherein the hydroxylated modified SEBS solution is prepared by mixing 6 to 12 parts by weight of hydroxylated modified SEBS and 90 to 180 parts by weight of xylene, the amount of isocyanate-based cross-linked polymer added is 5 to 13% of the mass of the hydroxylated modified SEBS solution, and the amount of dibutyltin dilaurate added is 2 to 8‰ of the mass of the hydroxylated modified SEBS solution;
[0008] Hydroxylation-modified SEBS is obtained by sequentially grafting and hydroxylating SEBS with maleic anhydride;
[0009] The raw materials of the isocyanate-based cross-linked polymer include: 20 to 40 parts by weight of diphenylmethane diisocyanate, 8 to 20 parts by weight of 2-amino-4-hydroxy-6-methylpyrimidine, 80 to 140 parts by weight of pyridine and 100 to 180 parts by weight of a precipitant;
[0010] The raw materials of the wear-resistant and anti-aging filler include: nano cerium oxide dispersion, isocyanate-based cross-linked polymer and dibutyltin dilaurate, wherein the nano cerium oxide dispersion is prepared by mixing 1 to 8 parts by weight of nano cerium oxide and 20 to 100 parts by weight of toluene, the added amount of the isocyanate-based cross-linked polymer is 4 to 15% of the mass of the nano cerium oxide dispersion, and the added amount of the dibutyltin dilaurate is 1 to 5‰ of the mass of the nano cerium oxide dispersion.
[0011] Further, the preparation of the composite TPE material specifically includes the following steps:
[0012] S1: Preparation of isocyanate-based cross-linked polymer: diphenylmethane diisocyanate, 2-amino-4-hydroxy-6-methylpyrimidine and pyridine are heated and stirred for reaction under a nitrogen atmosphere, and then a precipitant is added and stirred to generate a white precipitate. The white precipitate is filtered, washed and dried to obtain an isocyanate-based cross-linked polymer;
[0013] S2: Synthesis of cross-linked modified SEBS, after SEBS is grafted and modified by maleic anhydride, the obtained maleic anhydride modified SEBS is hydroxylated to obtain hydroxylated modified SEBS, and then, an isocyanate-based cross-linked polymer is reacted with the hydroxylated modified SEBS to obtain cross-linked modified SEBS;
[0014] S3: Preparation of wear-resistant and anti-aging filler: After nano-cerium oxide is dispersed in toluene, isocyanate-based cross-linked polymer and dibutyltin dilaurate are added, heated and stirred in a nitrogen atmosphere for reaction, filtered, washed and dried to obtain a wear-resistant and anti-aging filler;
[0015] S4: Mixing and processing,
[0016] The cross-linked modified SEBS and white oil are first stirred and mixed, and then polypropylene, ethylene-vinyl acetate copolymer, wear-resistant and anti-aging filler, antioxidant and lubricant are added. After stirring and mixing evenly, the mixture is extruded and granulated to obtain a composite TPE material.
[0017] Furthermore, the preparation of the isocyanate-based cross-linked polymer in step S1 specifically comprises the following steps:
[0018] Under a nitrogen atmosphere, 20 to 40 parts by weight of diphenylmethane diisocyanate, 8 to 20 parts by weight of 2-amino-4-hydroxy-6-methylpyrimidine and 80 to 140 parts by weight of pyridine are added to a reactor, heated to 96 to 110° C., stirred for reaction for 12 to 16 hours, 100 to 180 parts by weight of a precipitant are added, stirred for 5 to 15 minutes, a white precipitate is generated, the white precipitate is filtered out and washed with acetone and deionized water in turn, the washed white precipitate is placed in a vacuum drying oven at 56 to 64° C. and dried for 36 to 48 hours to obtain an isocyanate-based cross-linked polymer.
[0019] Furthermore, the precipitant is n-hexane.
[0020] Furthermore, step S2, the synthesis of cross-linked modified SEBS, specifically comprises the following steps:
[0021] S2.1: At 56-62° C., 6-10 parts by weight of SEBS are dissolved in 80-130 parts by weight of xylene to obtain a SEBS solution, and then 1-4 parts by weight of maleic anhydride and 0.2-1 parts by weight of benzoyl peroxide are added to the SEBS solution, heated to 100-110° C., stirred for reaction for 4-6 hours, and after the reaction is completed, a reaction solution A is obtained, and the reaction solution A is cooled to 30-38° C., washed 3-5 times with isopropanol whose volume is 3-5 times that of the reaction solution A, and then filtered and dried to obtain maleic anhydride-modified SEBS;
[0022] S2.2: At 95-105° C., 5-12 parts by weight of maleic anhydride-modified SEBS was dissolved in 90-180 parts by weight of xylene, 4-10 parts by weight of ethanolamine was added, and the mixture was heated to 130-150° C. and refluxed for 3-4 hours. After the reaction was completed, a reaction solution B was obtained. The reaction solution B was cooled to 30-38° C., and washed 3-5 times with isopropanol having a volume 3-5 times that of the reaction solution B. Subsequently, the mixture was filtered and dried to obtain a hydroxylated modified SEBS.
[0023] S2.3: Under the condition of 60-65°C, 6-12 parts by weight of hydroxylated modified SEBS are dissolved in 90-180 parts by weight of xylene to obtain a hydroxylated modified SEBS solution, and isocyanate-based cross-linked polymer and dibutyltin dilaurate are added to the hydroxylated modified SEBS solution, wherein the amount of isocyanate-based cross-linked polymer added is 5-13% of the mass of the hydroxylated modified SEBS solution, and the amount of dibutyltin dilaurate added is 2-8‰ of the mass of the hydroxylated modified SEBS solution. Under a nitrogen atmosphere, the reaction is stirred for 10-12 hours. After the reaction is completed, the obtained reaction solution C is poured into a polytetrafluoroethylene plate and allowed to stand at room temperature for 2-4 days to form a film. After the reaction solution C in the polytetrafluoroethylene plate forms a thin film, the formed thin film is taken out and dried and crushed to obtain a cross-linked modified SEBS.
[0024] Furthermore, step S3 of preparing the wear-resistant and anti-aging filler specifically comprises the following steps:
[0025] 1 to 8 parts by weight of nano-cerium oxide is added to 20 to 100 parts by weight of toluene, and ultrasonically dispersed for 3 to 5 minutes to obtain a nano-cerium oxide dispersion. An isocyanate-based cross-linked polymer is added to the nano-cerium oxide dispersion in an amount of 4 to 15% of the mass of the nano-cerium oxide dispersion. After stirring evenly, dibutyltin dilaurate is added in an amount of 1 to 5‰ of the mass of the nano-cerium oxide dispersion. The mixture is stirred at 75 to 85° C. for 4 to 6 hours under a nitrogen atmosphere. After the reaction is completed, the mixture is filtered, washed and dried to obtain a wear-resistant and anti-aging filler.
[0026] Furthermore, the particle size of nano-cerium oxide is 50 to 80 nm.
[0027] Furthermore, step S4 mixing and processing specifically includes the following steps:
[0028] 30-40 parts by weight of cross-linked modified SEBS and 32-45 parts by weight of white oil are first added into a high-speed mixer and stirred and mixed. Subsequently, 50-80 parts by weight of polypropylene, 10-25 parts by weight of ethylene-vinyl acetate copolymer, 3-12 parts by weight of wear-resistant and anti-aging fillers, 2-5 parts by weight of antioxidants and 1-3 parts by weight of lubricants are added into the high-speed mixer and stirred and mixed evenly to obtain a mixture. The mixture is extruded and granulated through a twin-screw extruder to obtain a composite TPE material.
[0029] Furthermore, the antioxidant is at least one of the antioxidant 1010 or the antioxidant 168 .
[0030] Furthermore, the lubricant is at least one of zinc stearate, magnesium stearate or calcium stearate.
[0031] Compared with the prior art, the present invention has at least the following advantages:
[0032] 1. In the present application, diphenylmethane diisocyanate and 2-amino-4-hydroxy-6-methylpyrimidine are used as raw materials, and an isocyanate group in diphenylmethane diisocyanate reacts with an amino group in 2-amino-4-hydroxy-6-methylpyrimidine to form a urea bond to obtain an isocyanate-based cross-linked polymer. The isocyanate-based cross-linked polymer has a cross-linked polymer structure that increases the interaction force between molecules, which is beneficial to improving the mechanical strength of its derivative materials. In addition, the benzene aromatic skeleton in the isocyanate-based cross-linked polymer can give its derivative materials better heat stability.
[0033] 2. In the present invention, the triblock structure SEBS is cross-linked and modified, so that the ethylene / butylene segment in the SEBS is grafted with maleic anhydride to obtain maleic anhydride modified SEBS, and then the anhydride group in the maleic anhydride modified SEBS is converted into a hydroxyl group to obtain a hydroxylated modified SEBS, and then the hydroxyl group in the hydroxylated modified SEBS reacts with the isocyanate group in the isocyanate cross-linked polymer to form a carbamate bond to obtain the cross-linked modified SEBS; the cross-linked modified SEBS can effectively improve the heat stability, aging corrosion resistance and mechanical strength of the SEBS through the introduction of the isocyanate cross-linked polymer, reduce the damage of the SEBS cross-linked structure caused by external force or high temperature, and ensure the stability of the SEBS cross-linked network.
[0034] 3. In the present invention, nano-cerium oxide is modified by using isocyanate-based cross-linked polymer, so that the hydroxyl group on the surface of nano-cerium oxide reacts with the isocyanate group in the isocyanate-based cross-linked polymer, and the obtained wear-resistant and anti-aging filler can be better evenly dispersed when added to the composite TPE material, thereby improving the wear resistance and anti-aging corrosion resistance of the composite TPE material. In addition, the isocyanate-based cross-linked polymer in the wear-resistant and anti-aging filler helps to improve the interchain interaction force between the wear-resistant and anti-aging filler and the cross-linked modified SEBS, forming a synergistic network between the wear-resistant and anti-aging filler and the cross-linked modified SEBS, thereby compensating for the reduction in mechanical properties and heat stability caused by oil replenishment. DETAILED DESCRIPTION
[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Example 1
[0037] A wear-resistant and corrosion-resistant composite TPE material for charging pile cables, specifically comprising the following steps:
[0038] S1: Preparation of isocyanate-based cross-linked polymers,
[0039] Under a nitrogen atmosphere, 40 parts by weight of diphenylmethane diisocyanate, 20 parts by weight of 2-amino-4-hydroxy-6-methylpyrimidine and 140 parts by weight of pyridine were added to a reactor, heated to 100° C., stirred for reaction for 16 hours, 180 parts by weight of n-hexane were added, stirred for 15 minutes, and a white precipitate was generated. The white precipitate was filtered out and washed with acetone and deionized water in turn, and the washed white precipitate was placed in a vacuum drying oven at 60° C. and dried for 48 hours to obtain an isocyanate-based cross-linked polymer;
[0040] S2: Synthesis of cross-linked modified SEBS,
[0041] S2.1: At 62° C., 10 parts by weight of SEBS were dissolved in 100 parts by weight of xylene to obtain a SEBS solution. Subsequently, 4 parts by weight of maleic anhydride and 1 part by weight of benzoyl peroxide were added to the SEBS solution, heated to 100° C., stirred for reaction for 6 hours, and after the reaction was completed, a reaction solution A was obtained. The reaction solution A was cooled to 35° C., washed 5 times with isopropanol whose volume was 5 times that of the reaction solution A, and then filtered and dried to obtain maleic anhydride-modified SEBS;
[0042] S2.2: At 105°C, 12 parts by weight of maleic anhydride-modified SEBS was dissolved in 180 parts by weight of xylene, 10 parts by weight of ethanolamine was added, and the mixture was heated to 140°C and refluxed for 4 hours. After the reaction was completed, a reaction solution B was obtained. The reaction solution B was cooled to 33°C, and washed 5 times with isopropanol having a volume 5 times that of the reaction solution B. Subsequently, the mixture was filtered and dried to obtain a hydroxylated modified SEBS.
[0043] S2.3: Under 65°C, 12 parts by weight of hydroxylated modified SEBS was dissolved in 180 parts by weight of xylene to obtain a hydroxylated modified SEBS solution, and isocyanate-based cross-linked polymer and dibutyltin dilaurate were added to the hydroxylated modified SEBS solution, wherein the amount of isocyanate-based cross-linked polymer added was 13% of the mass of the hydroxylated modified SEBS solution, and the amount of dibutyltin dilaurate added was 8‰ of the mass of the hydroxylated modified SEBS solution. The reaction was stirred for 12 hours under a nitrogen atmosphere. After the reaction was completed, the obtained reaction solution C was poured into a polytetrafluoroethylene plate and allowed to stand at room temperature for 4 days to form a film. After the reaction solution C in the polytetrafluoroethylene plate formed a thin film, the formed film was taken out and dried and crushed to obtain a cross-linked modified SEBS;
[0044] S3: Preparation of wear-resistant and anti-aging fillers,
[0045] 8 parts by weight of nano-cerium oxide with a particle size of 60 nm are added to 100 parts by weight of toluene, and ultrasonically dispersed for 5 minutes to obtain a nano-cerium oxide dispersion liquid, and an isocyanate-based cross-linked polymer is added to the nano-cerium oxide dispersion liquid, and the amount of the isocyanate-based cross-linked polymer added is 15% of the mass of the nano-cerium oxide dispersion liquid. After stirring evenly, dibutyltin dilaurate is added, and the amount of dibutyltin dilaurate added is 5‰ of the mass of the nano-cerium oxide dispersion liquid. Under a nitrogen atmosphere, the mixture is stirred at 80° C. for 6 hours. After the reaction is completed, the mixture is filtered, washed and dried to obtain a wear-resistant and anti-aging filler;
[0046] S4: Preparation of composite TPE materials,
[0047] 40 parts by weight of cross-linked modified SEBS and 45 parts by weight of white oil are first added into a high-speed mixer and stirred and mixed. Subsequently, 80 parts by weight of polypropylene, 25 parts by weight of ethylene-vinyl acetate copolymer, 12 parts by weight of wear-resistant and anti-aging filler, 5 parts by weight of antioxidant 1010 and 3 parts by weight of zinc stearate are added into the high-speed mixer and stirred and mixed evenly to obtain a mixture. The mixture is extruded and granulated through a twin-screw extruder to obtain a composite TPE material.
[0048] Example 2
[0049] A wear-resistant and corrosion-resistant composite TPE material for charging pile cables, specifically comprising the following steps:
[0050] S1: Preparation of isocyanate-based cross-linked polymers,
[0051] Under a nitrogen atmosphere, 40 parts by weight of diphenylmethane diisocyanate, 20 parts by weight of 2-amino-4-hydroxy-6-methylpyrimidine and 140 parts by weight of pyridine were added to a reactor, heated to 110° C., stirred for reaction for 12 h, 180 parts by weight of n-hexane were added, stirred for 5 min, a white precipitate was generated, the white precipitate was filtered out and washed with acetone and deionized water in turn, the washed white precipitate was placed in a vacuum drying oven at 56° C. and dried for 48 h to obtain an isocyanate-based cross-linked polymer;
[0052] S2: Synthesis of cross-linked modified SEBS,
[0053] S2.1: At 60° C., 10 parts by weight of SEBS were dissolved in 100 parts by weight of xylene to obtain a SEBS solution. Subsequently, 4 parts by weight of maleic anhydride and 1 part by weight of benzoyl peroxide were added to the SEBS solution, and the mixture was heated to 110° C. and stirred for reaction for 4 hours. After the reaction was completed, a reaction solution A was obtained. The reaction solution A was cooled to 30° C. and washed 5 times with isopropanol having a volume 5 times that of the reaction solution A. Subsequently, the solution was filtered and dried to obtain maleic anhydride-modified SEBS.
[0054] S2.2: At 100°C, 12 parts by weight of maleic anhydride-modified SEBS was dissolved in 180 parts by weight of xylene, 10 parts by weight of ethanolamine was added, and the mixture was heated to 150°C for reaction and refluxed for 3 hours. After the reaction was completed, a reaction solution B was obtained. The reaction solution B was cooled to 30°C, and washed 5 times with isopropanol having a volume 5 times that of the reaction solution B. Subsequently, the mixture was filtered and dried to obtain a hydroxylated modified SEBS.
[0055] S2.3: Under 60°C, 12 parts by weight of hydroxylated modified SEBS was dissolved in 180 parts by weight of xylene to obtain a hydroxylated modified SEBS solution, and isocyanate-based cross-linked polymer and dibutyltin dilaurate were added to the hydroxylated modified SEBS solution, wherein the amount of isocyanate-based cross-linked polymer added was 13% of the mass of the hydroxylated modified SEBS solution, and the amount of dibutyltin dilaurate added was 8‰ of the mass of the hydroxylated modified SEBS solution. The reaction was stirred for 10 hours under a nitrogen atmosphere. After the reaction was completed, the obtained reaction solution C was poured into a polytetrafluoroethylene plate and allowed to stand at room temperature for 4 days to form a film. After the reaction solution C in the polytetrafluoroethylene plate formed a thin film, the formed film was taken out and dried and crushed to obtain a cross-linked modified SEBS;
[0056] S3: Preparation of wear-resistant and anti-aging fillers,
[0057] 8 parts by weight of nano-cerium oxide with a particle size of 60 nm are added to 100 parts by weight of toluene, and ultrasonically dispersed for 3 minutes to obtain a nano-cerium oxide dispersion liquid, and an isocyanate-based cross-linked polymer is added to the nano-cerium oxide dispersion liquid, and the amount of the isocyanate-based cross-linked polymer added is 15% of the mass of the nano-cerium oxide dispersion liquid. After stirring evenly, dibutyltin dilaurate is added, and the amount of dibutyltin dilaurate added is 5‰ of the mass of the nano-cerium oxide dispersion liquid. Under a nitrogen atmosphere, the mixture is stirred at 75°C for 6 hours. After the reaction is completed, the mixture is filtered, washed and dried to obtain a wear-resistant and anti-aging filler;
[0058] S4: Preparation of composite TPE materials,
[0059] 40 parts by weight of cross-linked modified SEBS and 45 parts by weight of white oil are first added into a high-speed mixer and stirred and mixed. Subsequently, 80 parts by weight of polypropylene, 25 parts by weight of ethylene-vinyl acetate copolymer, 12 parts by weight of wear-resistant and anti-aging filler, 5 parts by weight of antioxidant 1010 and 3 parts by weight of zinc stearate are added into the high-speed mixer and stirred and mixed evenly to obtain a mixture. The mixture is extruded and granulated through a twin-screw extruder to obtain a composite TPE material.
[0060] Example 3
[0061] A wear-resistant and corrosion-resistant composite TPE material for charging pile cables, specifically comprising the following steps:
[0062] S1: Preparation of isocyanate-based cross-linked polymers,
[0063] Under a nitrogen atmosphere, 20 parts by weight of diphenylmethane diisocyanate, 8 parts by weight of 2-amino-4-hydroxy-6-methylpyrimidine and 80 parts by weight of pyridine were added to a reactor, heated to 100° C., stirred for reaction for 16 hours, 100 parts by weight of n-hexane were added, stirred for 15 minutes, and a white precipitate was generated. The white precipitate was filtered out and washed with acetone and deionized water in turn, and the washed white precipitate was placed in a vacuum drying oven at 60° C. and dried for 48 hours to obtain an isocyanate-based cross-linked polymer;
[0064] S2: Synthesis of cross-linked modified SEBS,
[0065] S2.1: At 62° C., 6 parts by weight of SEBS are dissolved in 100 parts by weight of xylene to obtain a SEBS solution. Subsequently, 2 parts by weight of maleic anhydride and 0.5 parts by weight of benzoyl peroxide are added to the SEBS solution, and the mixture is heated to 100° C. and stirred for reaction for 6 hours. After the reaction is completed, a reaction solution A is obtained. The reaction solution A is cooled to 35° C. and washed 5 times with isopropanol having a volume 5 times that of the reaction solution A. Subsequently, the solution is filtered and dried to obtain maleic anhydride-modified SEBS.
[0066] S2.2: At 105°C, 5 parts by weight of maleic anhydride-modified SEBS was dissolved in 100 parts by weight of xylene, and 5 parts by weight of ethanolamine was added, and the mixture was heated to 140°C and refluxed for 4 hours. After the reaction was completed, a reaction solution B was obtained. The reaction solution B was cooled to 33°C, and washed 5 times with isopropanol having a volume 5 times that of the reaction solution B. Subsequently, the mixture was filtered and dried to obtain a hydroxylated modified SEBS.
[0067] S2.3: Under 65°C, 6 parts by weight of hydroxylated modified SEBS were dissolved in 100 parts by weight of xylene to obtain a hydroxylated modified SEBS solution, and isocyanate-based cross-linked polymer and dibutyltin dilaurate were added to the hydroxylated modified SEBS solution, wherein the amount of isocyanate-based cross-linked polymer added was 7% of the mass of the hydroxylated modified SEBS solution, and the amount of dibutyltin dilaurate added was 2‰ of the mass of the hydroxylated modified SEBS solution. The reaction was stirred for 12 hours under a nitrogen atmosphere. After the reaction was completed, the obtained reaction solution C was poured into a polytetrafluoroethylene plate and allowed to stand at room temperature for 4 days to form a film. After the reaction solution C in the polytetrafluoroethylene plate formed a thin film, the formed film was taken out and dried and crushed to obtain a cross-linked modified SEBS;
[0068] S3: Preparation of wear-resistant and anti-aging fillers,
[0069] 1 part by weight of nano-cerium oxide with a particle size of 60 nm is added to 20 parts by weight of toluene, and ultrasonically dispersed for 5 minutes to obtain a nano-cerium oxide dispersion liquid, and an isocyanate-based cross-linked polymer is added to the nano-cerium oxide dispersion liquid, and the amount of the isocyanate-based cross-linked polymer added is 10% of the mass of the nano-cerium oxide dispersion liquid. After stirring evenly, dibutyltin dilaurate is added, and the amount of dibutyltin dilaurate added is 1‰ of the mass of the nano-cerium oxide dispersion liquid. Under a nitrogen atmosphere, the mixture is stirred at 80° C. for 6 hours. After the reaction is completed, the mixture is filtered, washed and dried to obtain a wear-resistant and anti-aging filler;
[0070] S4: Preparation of composite TPE materials,
[0071] 40 parts by weight of cross-linked modified SEBS and 45 parts by weight of white oil are first added into a high-speed mixer and stirred and mixed. Subsequently, 80 parts by weight of polypropylene, 25 parts by weight of ethylene-vinyl acetate copolymer, 6 parts by weight of wear-resistant and anti-aging filler, 5 parts by weight of antioxidant 1010 and 3 parts by weight of zinc stearate are added into the high-speed mixer and stirred and mixed evenly to obtain a mixture. The mixture is extruded and granulated through a twin-screw extruder to obtain a composite TPE material.
[0072] Comparative Example 1
[0073] Compared with Example 1, the difference of Comparative Example 1 is that step S2 is removed, the cross-linked modified SEBS in step S4 is replaced by SEBS, and the other steps remain unchanged to prepare a composite TPE material, which is recorded as Comparative Example 1.
[0074] Comparative Example 2
[0075] Compared with Example 1, the difference of Comparative Example 2 is that step S3 is removed, the wear-resistant and anti-aging filler in step S4 is replaced by nano cerium oxide, and the other steps remain unchanged to prepare a composite TPE material, which is recorded as Comparative Example 2.
[0076] Comparative Example 3
[0077] Compared with Example 1, the difference of Comparative Example 3 is that step S2 and step S3 are removed, the cross-linked modified SEBS in step S4 is replaced by SEBS, the wear-resistant and anti-aging filler is replaced by nano-cerium oxide, and the other steps remain unchanged to prepare a composite TPE material, which is recorded as Comparative Example 3.
[0078] The mechanical properties of the composite TPE materials in Examples 1-3 and Comparative Examples 1-3 were tested according to GB / T528-2009 standard. The mechanical properties results are shown in Table 1.
[0079] Table 1:
[0080] Group Tensile strength(MPa) Elongation at break (%) Example 1 21.4 752 Example 2 20.7 744 Example 3 21.1 757 Comparative Example 1 18.8 706 Comparative Example 2 17.3 671 Comparative Example 3 13.6 539
[0081] As shown in Table 1, the tensile strength and elongation at break test results of the composite TPE materials of Examples 1-3 are better than those of Comparative Examples 1-3, the tensile strength can reach above 20Mpa, and the elongation at break can reach above 740%, and the composite TPE materials have good mechanical properties. This indicates that the cross-linked modified SEBS and the wear-resistant and anti-aging filler are more conducive to improving the mechanical strength of the composite TPE material than SEBS and the unmodified nano-cerium oxide, and the isocyanate-based cross-linked polymer components in the cross-linked modified SEBS and the wear-resistant and anti-aging filler both play a role in assisting in improving the mechanical properties of the composite TPE material.
[0082] Some of the composite TPE materials in Examples 1-3 and Comparative Examples 1-3 were selected for hot air aging treatment. The specific operation was as follows: the composite TPE material was heat-treated in hot air at 90° C. for 168 hours, and then the mechanical properties of the composite TPE material after hot air aging treatment were tested, and the changes in the mechanical properties of the composite TPE material before and after hot air aging treatment were calculated. The tensile strength change rate of the composite TPE material after hot air aging treatment was calculated as follows: A (%) = (tensile strength before hot air aging treatment - tensile strength after hot air aging treatment) / tensile strength before hot air aging treatment * 100%; the elongation at break of the composite TPE material after hot air aging treatment was calculated as follows: B = (elongation at break before hot air aging treatment - elongation at break after hot air aging treatment) / elongation at break before hot air aging treatment * 100%, and the results are shown in Table 2;
[0083] Part of the composite TPE materials in Examples 1-3 and Comparative Examples 1-3 were subjected to ultraviolet irradiation treatment. The specific operation was as follows: a UVA-340 light source was used with an irradiation intensity of (0.85±0.02) W / m 2 , the wavelength was controlled to be 340nm, the treatment time was 1000h, and the treatment process included a cycle of 8h of ultraviolet irradiation (70°C) / 4h of condensation (50°C). Subsequently, the mechanical properties of the composite TPE material treated with ultraviolet irradiation were tested, and the changes in the mechanical properties of the composite TPE material before and after ultraviolet irradiation were calculated. The calculation formula for the change rate of tensile strength of the composite TPE material after ultraviolet irradiation treatment was: C(%) = (tensile strength before ultraviolet irradiation treatment - tensile strength after ultraviolet irradiation treatment) / tensile strength before ultraviolet irradiation treatment * 100%; the calculation formula for the change rate of elongation at break of the composite TPE material after ultraviolet irradiation treatment was: D = (elongation at break before ultraviolet irradiation treatment - elongation at break after ultraviolet irradiation treatment) / elongation at break before ultraviolet irradiation treatment * 100%. The results are shown in Table 2.
[0084] Table 2:
[0085]
[0086] As shown in Table 2, whether after hot air aging treatment or ultraviolet irradiation treatment, the tensile strength change rate and elongation at break change rate of the composite TPE materials of Examples 1-3 are less than those of the composite TPE materials of Comparative Examples 1-3, that is, the composite TPE materials of Examples 1-3 have stronger thermal stability and weathering and aging corrosion resistance than those of Comparative Examples 1-3. It can be seen that the cross-linked modified SEBS and the wear-resistant and anti-aging filler in the composite TPE material can effectively ensure that the composite TPE material still maintains relatively good mechanical properties after hot air aging treatment and ultraviolet irradiation, among which the cross-linked modified SEBS in the composite TPE material plays a significant role in thermal stability, and the wear-resistant and anti-aging filler in the composite TPE material plays a major role in ultraviolet weathering and corrosion resistance.
[0087] The wear resistance of the composite TPE materials in Examples 1-3 and Comparative Examples 1-3 was tested according to GB / T1689-1998. The samples of each group of composite TPE materials were respectively pasted on different rubber wheels, and rolled for 600 r. The weight of each group of sample rubber wheels was weighed and recorded as m0. Subsequently, the sample rubber wheels after pre-grinding and weighing continued to be subjected to a rolling friction test. When the friction mileage was 1.5 km, the sample rubber wheels of each group were weighed and recorded as m1, and the wear rate was calculated. The wear rate calculation formula is: T (%) = (m0-m1) / m0*100%. The wear resistance test results are shown in Table 3;
[0088] Table 3:
[0089] Group Wear rate (%) Example 1 0.79% Example 2 0.77% Example 3 0.81% Comparative Example 1 0.92% Comparative Example 2 1.25% Comparative Example 3 1.34%
[0090] As shown in Table 3, after the rolling friction test, the wear rate of Examples 1-3 is less than 0.9%, and the test results are significantly better than those of Comparative Examples 2-3, indicating that, compared with nano cerium oxide, the use of wear-resistant and anti-aging fillers as fillers for composite TPE materials is more conducive to improving the wear resistance of composite TPE materials.
[0091] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all such improvements and changes should fall within the scope of protection of the appended claims of the present invention. Parts not described in detail in this specification belong to the prior art known to those skilled in the art.
Claims
1. A wear-resistant and corrosion-resistant composite TPE material for charging pile cables, characterized in that: Composite TPE materials are composed of the following components: 50-80 parts by weight of polypropylene, 30-40 parts by weight of crosslinked modified SEBS, 32-45 parts by weight of white oil, 10-25 parts by weight of ethylene-vinyl acetate copolymer, 3-12 parts by weight of wear-resistant and anti-aging filler, 2-5 parts by weight of antioxidant and 1-3 parts by weight of lubricant; The raw materials of cross-linked modified SEBS include: hydroxylated modified SEBS solution, isocyanate-based cross-linked polymer and dibutyltin dilaurate, wherein the hydroxylated modified SEBS solution is prepared by mixing 6 to 12 parts by weight of hydroxylated modified SEBS and 90 to 180 parts by weight of xylene, the amount of isocyanate-based cross-linked polymer added is 5 to 13% of the mass of the hydroxylated modified SEBS solution, and the amount of dibutyltin dilaurate added is 2 to 8‰ of the mass of the hydroxylated modified SEBS solution; Hydroxylation-modified SEBS is obtained by sequentially grafting and hydroxylating SEBS with maleic anhydride; The raw materials of the isocyanate-based cross-linked polymer include: 20 to 40 parts by weight of diphenylmethane diisocyanate, 8 to 20 parts by weight of 2-amino-4-hydroxy-6-methylpyrimidine, 80 to 140 parts by weight of pyridine and 100 to 180 parts by weight of a precipitant; The raw materials of the wear-resistant and anti-aging filler include: nano cerium oxide dispersion, isocyanate-based cross-linked polymer and dibutyltin dilaurate, wherein the nano cerium oxide dispersion is prepared by mixing 1 to 8 parts by weight of nano cerium oxide and 20 to 100 parts by weight of toluene, the added amount of the isocyanate-based cross-linked polymer is 4 to 15% of the mass of the nano cerium oxide dispersion, and the added amount of the dibutyltin dilaurate is 1 to 5‰ of the mass of the nano cerium oxide dispersion.
2. The wear-resistant and corrosion-resistant composite TPE material for charging pile cables according to claim 1, characterized in that: The preparation of the composite TPE material specifically includes the following steps: S1: Preparation of isocyanate-based cross-linked polymer: diphenylmethane diisocyanate, 2-amino-4-hydroxy-6-methylpyrimidine and pyridine are heated and stirred for reaction under a nitrogen atmosphere, and then a precipitant is added and stirred to generate a white precipitate. The white precipitate is filtered, washed and dried to obtain an isocyanate-based cross-linked polymer; S2: Synthesis of cross-linked modified SEBS, after SEBS is grafted and modified by maleic anhydride, the obtained maleic anhydride modified SEBS is hydroxylated to obtain hydroxylated modified SEBS, and then, an isocyanate-based cross-linked polymer is reacted with the hydroxylated modified SEBS to obtain cross-linked modified SEBS; S3: Preparation of wear-resistant and anti-aging filler: After nano-cerium oxide is dispersed in toluene, isocyanate-based cross-linked polymer and dibutyltin dilaurate are added, heated and stirred in a nitrogen atmosphere for reaction, filtered, washed and dried to obtain a wear-resistant and anti-aging filler; S4: Mixing and processing, The cross-linked modified SEBS and white oil are first stirred and mixed, and then polypropylene, ethylene-vinyl acetate copolymer, wear-resistant and anti-aging filler, antioxidant and lubricant are added. After stirring and mixing evenly, the mixture is extruded and granulated to obtain a composite TPE material.
3. The wear-resistant and corrosion-resistant composite TPE material for charging pile cables according to claim 2, characterized in that: Step S1 isocyanate-based cross-linked polymer preparation, specifically comprising the following steps: Under a nitrogen atmosphere, 20 to 40 parts by weight of diphenylmethane diisocyanate, 8 to 20 parts by weight of 2-amino-4-hydroxy-6-methylpyrimidine and 80 to 140 parts by weight of pyridine are added to a reactor, heated to 96 to 110° C., stirred for reaction for 12 to 16 hours, 100 to 180 parts by weight of a precipitant are added, stirred for 5 to 15 minutes, a white precipitate is generated, the white precipitate is filtered out and washed with acetone and deionized water in turn, the washed white precipitate is placed in a vacuum drying oven at 56 to 64° C. and dried for 36 to 48 hours to obtain an isocyanate-based cross-linked polymer.
4. The wear-resistant and corrosion-resistant composite TPE material for charging pile cables according to claim 3, characterized in that: The precipitant was n-hexane.
5. The wear-resistant and corrosion-resistant composite TPE material for charging pile cables according to claim 2, characterized in that: Step S2: Synthesis of cross-linked modified SEBS, specifically comprising the following steps: S2.1: At 56-62° C., 6-10 parts by weight of SEBS are dissolved in 80-130 parts by weight of xylene to obtain a SEBS solution, and then 1-4 parts by weight of maleic anhydride and 0.2-1 parts by weight of benzoyl peroxide are added to the SEBS solution, heated to 100-110° C., stirred for reaction for 4-6 hours, and after the reaction is completed, a reaction solution A is obtained, and the reaction solution A is cooled to 30-38° C., washed 3-5 times with isopropanol whose volume is 3-5 times that of the reaction solution A, and then filtered and dried to obtain maleic anhydride-modified SEBS; S2.2: At 95-105° C., 5-12 parts by weight of maleic anhydride-modified SEBS was dissolved in 90-180 parts by weight of xylene, 4-10 parts by weight of ethanolamine was added, and the mixture was heated to 130-150° C. and refluxed for 3-4 hours. After the reaction was completed, a reaction solution B was obtained. The reaction solution B was cooled to 30-38° C., and washed 3-5 times with isopropanol having a volume 3-5 times that of the reaction solution B. Subsequently, the mixture was filtered and dried to obtain a hydroxylated modified SEBS. S2.3: Under the condition of 60-65°C, 6-12 parts by weight of hydroxylated modified SEBS are dissolved in 90-180 parts by weight of xylene to obtain a hydroxylated modified SEBS solution, and isocyanate-based cross-linked polymer and dibutyltin dilaurate are added to the hydroxylated modified SEBS solution, wherein the amount of isocyanate-based cross-linked polymer added is 5-13% of the mass of the hydroxylated modified SEBS solution, and the amount of dibutyltin dilaurate added is 2-8‰ of the mass of the hydroxylated modified SEBS solution. Under a nitrogen atmosphere, the reaction is stirred for 10-12 hours. After the reaction is completed, the obtained reaction solution C is poured into a polytetrafluoroethylene plate and allowed to stand at room temperature for 2-4 days to form a film. After the reaction solution C in the polytetrafluoroethylene plate forms a thin film, the formed thin film is taken out and dried and crushed to obtain a cross-linked modified SEBS.
6. The wear-resistant and corrosion-resistant composite TPE material for charging pile cables according to claim 2, characterized in that: Step S3 is the preparation of wear-resistant and anti-aging filler, which specifically comprises the following steps: 1 to 8 parts by weight of nano-cerium oxide is added to 20 to 100 parts by weight of toluene, and ultrasonically dispersed for 3 to 5 minutes to obtain a nano-cerium oxide dispersion. An isocyanate-based cross-linked polymer is added to the nano-cerium oxide dispersion in an amount of 4 to 15% of the mass of the nano-cerium oxide dispersion. After stirring evenly, dibutyltin dilaurate is added in an amount of 1 to 5‰ of the mass of the nano-cerium oxide dispersion. The mixture is stirred at 75 to 85° C. for 4 to 6 hours under a nitrogen atmosphere. After the reaction is completed, the mixture is filtered, washed and dried to obtain a wear-resistant and anti-aging filler.
7. The wear-resistant and corrosion-resistant composite TPE material for charging pile cables according to claim 6, characterized in that: The particle size of nano cerium oxide is 50 to 80 nm.
8. The wear-resistant and corrosion-resistant composite TPE material for charging pile cables according to claim 2, characterized in that: Step S4 is a mixing process, which specifically includes the following steps: 30-40 parts by weight of cross-linked modified SEBS and 32-45 parts by weight of white oil are first added into a high-speed mixer and stirred and mixed. Subsequently, 50-80 parts by weight of polypropylene, 10-25 parts by weight of ethylene-vinyl acetate copolymer, 3-12 parts by weight of wear-resistant and anti-aging fillers, 2-5 parts by weight of antioxidants and 1-3 parts by weight of lubricants are added into the high-speed mixer and stirred and mixed evenly to obtain a mixture. The mixture is extruded and granulated through a twin-screw extruder to obtain a composite TPE material.
9. The wear-resistant and corrosion-resistant composite TPE material for charging pile cables according to claim 8, characterized in that: The antioxidant is at least one of the antioxidant 1010 and the antioxidant 168 .
10. The wear-resistant and corrosion-resistant composite TPE material for charging pile cables according to claim 8, characterized in that: The lubricant is at least one of zinc stearate, magnesium stearate or calcium stearate.
Citation Information
Patent Citations
Wear-resistant SEBS thermoplastic elastomer material and preparation method thereof
CN105566924A
Uniform and stable wear-resistant TPE material and preparation method thereof
CN115246978A
Crosslinked halogen-free flame-retardant TPE material and preparation method thereof
CN115991925A
Wear-resistant PP film for calcium silicate board
CN116903956A
Preparation method of ultraviolet-proof TPE (thermoplastic elastomer) material
CN119177002A